(untitled) (Research, Society and Development, 2024)
Canine distemper is a highly contagious disease caused by a virus belonging to the Paramyxoviridae family, of the Morbillivirus genus. It affects a wide variety of hosts in addition to domestic dogs. This virus has a high incidence in young animals and is characterized by a high mortality rate. Unvaccinated dogs or those with an incomplete vaccination protocol, with a history of contact with infected animals, and maternal colostrum with low antibodies are affected. Transmission can occur through direct contact, ingestion of food, contaminated objects and even through the dispersion of aerosols. The objective of this study is to present a narrative review of canine distemper. Among infectious diseases, it is considered the second leading cause of death among dogs, second only to rabies. Inflammatory and infectious diseases of the Central Nervous System (CNS) constitute a relevant group of pathologies that affect dogs, frequently associated with severe clinical signs, often incompatible with the survival of the animal, and which can originate from various etiologies. The most common symptoms are neurological in origin, although respiratory, skin and gastrointestinal manifestations may also be observed. Therefore, diagnosis consists of evaluating the symptoms presented in conjunction with specific tests, such as viral isolation, ELISA, immunofluorescence and RT-PCR. Currently, there is no specific treatment available, with only palliative care being provided. Therefore, vaccination represents the most effective method for reducing the risk of developing the disease, since the lack of vaccination can increase the probability of its occurrence by approximately one hundred times.